Concurrent validity of the combined HRV/ACC sensor and physical activity diary when monitoring physical activity in university students during free-living days - Liu, Haochong; Li, Qian; Li, Yiting; Wang, Yubo; Huang, Yaling; Bao, Dapeng; Liu, Haoyang; Cui, Yixiong (Frontiers in Public Health, 2022)
The purpose of this research was to determine if the commercially available combined HR and ACC device (Firstbeat Bodyguard 2, BG2) was valid and reliable of energy expenditure and time spend in different intensity zones in free-living. Fifty-five healthy participants performed 48-hour PA monitoring with BG2, ActiGraph GT3X+ and Bouchard Physical Activity Diary. To evaluate the performance, the difference, correlation and agreement of the TEE, PAEE, SD, LPA, MVPA, as well as the Bland-Altman plots of these parameters were drawed. The results shown that the estimated of TEE and PAEE from Bouchard Physical Activity Diary were highest, ActiGraph GT3X+ were lowest, and BG2 were intermediate. The highest correlation was shown in energy expenditure (r = 0.469 to 0.902), the agreement in all kinds of time spend of different intensity zones was generally poor (τ=0.017 to 0.371 ；ICC= -0.001 to 0.479). Our findings showed that the BG2 might be utilized to estimated the energy expenditure and time spend in different intensity zones in free-living.